2011
DOI: 10.1007/s00213-011-2255-y
|View full text |Cite
|
Sign up to set email alerts
|

Dexamphetamine effects on separate constructs in the rubber hand illusion test

Abstract: These results show a novel pharmacological manipulation of separate constructs of the RHI. This finding may aid in our understanding of disorders that have overlapping disturbances in both dopamine activity and body representations, particularly schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 104 publications
7
32
1
1
Order By: Relevance
“…Using an amphetamine challenge in healthy volunteers as a model of psychoses-related responses in the rubber-hand illusion, our group (44) found that amphetamine appeared to increase the temporal envelope of associability of the rubber-hand visual cues to the feel of the stroking (i.e., had a selective effect of increasing the illusion in the asynchronous condition) in a profile of performance, which was similar to the pattern of performance in the Current group. Together with their functional role of assigning salience to external stimuli (35), dopaminergic pathways may well contribute to confusion, and misattribution, of agency via changes in the normal temporal window for associability such that external cues become a possible source of body input.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Using an amphetamine challenge in healthy volunteers as a model of psychoses-related responses in the rubber-hand illusion, our group (44) found that amphetamine appeared to increase the temporal envelope of associability of the rubber-hand visual cues to the feel of the stroking (i.e., had a selective effect of increasing the illusion in the asynchronous condition) in a profile of performance, which was similar to the pattern of performance in the Current group. Together with their functional role of assigning salience to external stimuli (35), dopaminergic pathways may well contribute to confusion, and misattribution, of agency via changes in the normal temporal window for associability such that external cues become a possible source of body input.…”
Section: Discussionmentioning
confidence: 57%
“…Psychometric studies show that illusory sensations over the “other” hand are simultaneously associated with a reduction of the same sensations in the real hand (43). For example, embodiment of the “other” hand is proportionally related to disembodiment of one’s real hand, with the total embodiment of both being equal to one single hand (44, 45). A similar balance also exists with the sense of agency (46).…”
Section: Introductionmentioning
confidence: 99%
“…The resting-state procedure testing began at 200 min post-dose, shortly after the reference peak dexamphetamine concentration for oral administration of 25 mg [Asghar et al, 2003]. This is also close to the peak time of the autonomic effects of Figure 1 from Albrecht et al, 2011b]. Due to the complex relationships observed between heart rate and EEG [e.g., Lechinger et al, 2015;Dirlich et al, 1998], we report here the heart rate increase in response to amphetamine.…”
Section: Participantsmentioning
confidence: 73%
“…Conversely, D 2 R levels in cortical and striatal areas correlate with positive but not negative symptom scores (Kessler et al, 2009). Nevertheless, some trait-like phenomena can be reproduced by both ketamine and dopaminergic agonists, such as reduced latent inhibition (Young et al, 2005; Razoux et al, 2007), blocking (O’Tuathaigh et al, 2003; Freeman et al, 2013), and the body ownership illusion (Albrecht et al, 2011; Morgan et al, 2011). This is not surprising, as there are complex interactions between glutamatergic, GABAergic, and dopaminergic neurotransmission, within and between the brain stem, striatum, and prefrontal cortex (see Figure 2).…”
Section: The Psychopharmacology Of Precisionmentioning
confidence: 99%